PERSEPSI MAHASISWA PADA FILM MENCURI RADEN SALEH DI KOTA SURAKARTA DENGAN MENAMPILKAN FILM GENRE HEIST DI INDONESIA - Febryan Saweho, Ellfando; Suryo S, Herning; Herawati, Dewi Maria (Solidaritas, 2024)
Perception is a process that is prioritized through sensing, namely in a process that will be received by individuals through a receptor, namely the sensory organs in the body. So that in this sensing process it will not be separated from the process of a perception. Even perception is a very important concept in psychology, Perception, according to Jalaluddin Rakhmat, is the experience of an object, event, or relationship that is obtained by inferring information and interpreting a message. This research is shown to dissect the movie Mencuri Raden Saleh which was made in 2022 by Visinema Pictures Jakarta and provide perceptual responses to students in Surakarta. The theory used in this research is using the theory of Dr. Jalaluddin Rakhmat, M.Sc. Which is about the perception of communication psychology. The method used in this research is descriptive qualitative. Meanwhile, to dissect the meaning in the film Stealing Raden Saleh and find out the perception, using the theory of Dr. Jalaluddin Rakhmat, M.Sc, namely the perception of communication psychology that seeks the meaning of motivation, experience, personality, and the process of impression formation. The data used in this study, namely, the type of premier data taken through each perception of the informant during the research and secondary data in the form of journals, articles, and interviews to support this research so that there is no data subjectivity. The validity of the data used in this study uses data triangulation. The results of this study, the film Mencuri Raden Saleh is set in a heist film in Indonesia and raises figures from Indonesian history, namely, Raden Saleh and his famous painting of the capture of Prince Diponegoro 1857. Resulting in a perception of Communication Science Study Program students at Slamet Riyadi University Surakarta who are very enthusiastic and like the film Stealing Raden Saleh. Keywords : Perception, Film Heist Genre, Raden Saleh Sjarif Boestaman